Robert Kroetsch essays on his works - Markotić, Nicole 1962- (Guernica Editions, 2017)
"These essays span the period of Kroetsch's writing. Included are essays that cover (some of) his novels, (some of) his poetry, and even (some of) his critical writing. The contributors include writers who knew Kroetsch well and those who only met him on the page; critics at the beginning of their careers and those well established in the Canadian literary field, men and women, writers and poets and critics and damn fine thinkers."--Provided by publisher
Keywords: Kroetsch, Robert -- 1927-2011; Kroetsch, Robert / 1927-2011 / Criticism and interpretation; Kroetsch, Robert / 1927-2011 / Critique et interprétation; Kroetsch, Robert / 1927-2011; Criticism, interpretation, etc; Aufsatzsammlung